Wear Resistance and Bond Strength of Plasma Sprayed Fe/Mo Amorphous Coatings - JIANG, Chao-ping; XING, Ya-zhe; ZHANG, Feng-ying; HAO, Jian-min; SONG, Xu-cling (Journal of iron and steel research, international, 2014)
Fe-based and Fe/Mo composite amorphous coatings were deposited on the surface of plain carbon steel substrates by atmospheric plasma spraying （APS）. With increasing the Mo alloy content, the microstructure of the coatings revealed more dense structure. The porosities of composite coating were all less than those of Fe-based coat- ing due to Mo alloy self-bonding performance. The ML10 friction and wear tester was employed to investigate the wear behaviors of the coatings under dry sliding conditions. It was found that the mass loss of the resultant coatings decreased with increasing Mo-based powders into the feedstock. This was attributed to the reduction of the delamina- tions resulting from improved intersplat bond with Mo addition.